CKD Increases the Risk of Age-Related Macular Degeneration - Liew, Gerald (American Society of Nephrology, 2008)
Age-related macular degeneration is the leading cause of irreversible blindness in the United States and often coexists with chronic kidney disease. Both conditions share common genetic and environmental risk factors. A total of 1183 participants aged 54+ were examined in the population-based, prospective cohort Blue Mountains Eye Study (Australia) to determine if chronic kidney disease increases the risk of age-related macular degeneration. Moderate chronic kidney disease (estimated glomerular filtration rate < 60 ml/min per 1.73 m(2) based on the Cockcroft-Gault equation) was present in 24% of the population (286 of 1183). The 5-yr incidence of early age-related macular degeneration was 3.9% in participants with no/mild chronic kidney disease (35 of 897) and 17.5% in those with moderate chronic kidney disease (50 of 286). After adjusting for age, sex, cigarette smoking, hypertension, complement factor H polymorphism, and other risk factors, persons with moderate chronic kidney disease were 3 times more likely to develop early age-related macular degeneration than persons with no/mild chronic kidney disease (odds ratio = 3.2; 95% confidence interval, 1.8 to 5.7, P < 0.0001). Each SD (14.8 ml/min per 1.73 m(2)) decrease in Cockcroft-Gault estimated glomerular filtration rate was associated with a doubling of the adjusted risk for early age-related macular degeneration (odds ratio = 2.0; 95% confidence interval, 1.5 to 2.8, P < 0.0001). In conclusion, persons with chronic kidney disease have a higher risk of early age-related macular degeneration, suggesting the possibility of shared pathophysiologic mechanisms between the two conditions.